Pengembangan Media Pembelajaran Matematika dengan Macromedia Flash Pada Siswa SMP Muhammadiyah Ternate - Asmira Sudiman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research and development aims 1) to determine the feasibility of developing mathematics learning media using the Macromedia Flash application program, 2) to determine the attractiveness of student responses to the development of mathematics learning media using the Macromedia Flash application program. This research was conducted using the Research & Development (R & D) method using the modified Borg & Gall development procedure, namely 10 stages, limited to the 7th stage. Data collection techniques using validation questionnaire sheets. The instrument used is a validation questionnaire sheet to determine the feasibility of the module and a student response questionnaire to determine attractiveness. The data analysis technique used in research and development is descriptive quantitative to process data in the form of scores from assessments by the validator and student responses, while descriptive qualitative is to describe the data in the form of comments suggesting improvements from the validator. Based on the validation results for the development of mathematics learning media using the macromedia flash application program, an average score is obtained; (1) the feasibility of developing mathematics learning media using the macromedia flash application program validation results from material experts obtained an average of 3.73, on the linguistic aspect an average of 3.64, on the evaluation feasibility aspect an average of 3.66, media experts obtained an average score (the media efficiency aspect obtained an average score of 3.87, the button function aspect obtained an average score of 3.5 and the Graphic aspect obtained an average score of 3.4). The product validation results are in the feasible criteria, (2) the attractiveness of the development of mathematics learning media using the macromedia flash application program student responses obtained an average score of 3.61 in the "very interesting" criterion.